I. Ya. DZYRA: TURKISH ELEMENTS IN THE 1756 REGISTER OF THE ZAPOROZHIAN HOST Summary. Introduction - DZYRA, I. Ya. (Linguistic Bulletin (Movoznavchyi Visnyk), 2021)
Summary. Introduction. For a long time, the Zaporоzhian region was a natural ethnocontact territory between the Ukrainian and Turkic peoples. Therefore the complex study of the anthroponymycal system of Zaporozhian Cossacks is impossible without research of the Turkic elements, which used for person’s identification on Zaporozhian Sich. The purpose of this article is to study the Turkic lexical borrowings in the anthroponymic system of the Zaporozhian Cossacks in the middle of the XVIII century. Its solution involves establishing the total number of family names, performing their lexical and semantic characteristics, as well as clarifying the word-forming activity of the Turkic elements. Results. In total, 105 anthroponymic Turkisms were found on the pages of the 1756 Register of the Zaporozhian Host. Their bearers are 415 persons, which is 2,77 % of the total number named. Given the nature of the nomination processes, all foreign language elements are divided into exogenous and homogeneous. The first group includes those Turkic anthropolexems that were directly transferred to the Ukrainian anthroponymic system (17 family names, 68 bearers). These are simple or two-rooted Turkic personal names used as the second distinguishing element in the composition of two-parted proper anthroponymic names. Instead, endogenous Turkisms were formed either by transonymization (6 family names, 10 bearers), or from Turkic appellatives assimilated in the Ukrainian language (82 family names, 337 bearers), among which we distinguish 22 lexical-semantic subgroups. Originality. In the article the peculiarities of the family names, which made from Turkic elements in the 1756 Register of the Zaporozhian Host, is presented for the first time. Conclusions. In the process of formation of the family names of Zaporozhian Cossacks the Turkic antroponyms enjoyed by very inferior degree of the antroponymyzation. On the other hand, Turkic appellatives assimilated into Ukrainian were more widely used to identify a person among the Zaporozhian Cossacks. Analysis of the register shows that the replenishment of the Ukrainian anthroponymicon in the XVIII century with Turkic elements were a living linguistic process, during which they underwent grammatical adaptation, acquired new or additional meanings, became the basis for the creation of diminutives, and so on.